Molecular Research in Aquaculture - Ken Overturf (2009)

(untitled)
The aim of this book is to provide a basic understanding of the modern molecular techniquescurrentlyusedinaquacultureresearch,primarilyï¬nï¬shaquaculture,such that readers can develop an understanding of both the power and limitations of molecular biology. Recently, in the scientiï¬c literature, there has been a profusion of information pertaining to genetics, genomics, transcriptomics, proteomics, and otherrelatedbuzzwordsmeanttodescribemolecularresearchrelatingcellularevents to physiological traits.